Proteomics of tumor and serum samples from isocitrate dehydrogenase‐wildtype glioblastoma patients: is the detoxification of reactive oxygen species associated with shorter survival? - Anne Clavreul; Catherine Guette; Hamza Lasla; Audrey Rousseau; Odile Blanchet; Cécile Henry; Alice Boissard; Mathilde Cherel; Pascal Jézéquel; François Guillonneau; Philippe Menei; Jean‐Michel Lemée (Molecular Oncology)
Proteomics has been little used for the identification of novel prognostic and/or therapeutic markers in isocitrate dehydrogenase (IDH)‐wildtype glioblastoma (GB). In this study, we analyzed 50 tumor and 30 serum samples from short‐ and long‐term survivors of IDH‐wildtype GB (STS and LTS, respectively) by data‐independent acquisition mass spectrometry (DIA‐MS)‐based proteomics, with the aim of identifying such markers. DIA‐MS identified 5422 and 826 normalized proteins in tumor and serum samples, respectively, with only three tumor proteins and 26 serum proteins displaying significant differential expression between the STS and LTS groups. These dysregulated proteins were principally associated with the detoxification of reactive oxygen species (ROS). In particular, GB patients in the STS group had high serum levels of malate dehydrogenase 1 (MDH1) and ribonuclease inhibitor 1 (RNH1) and low tumor levels of fatty acid‐binding protein 7 (FABP7), which may have enabled them to maintain low ROS levels, counteracting the effects of the first‐line treatment with radiotherapy plus concomitant and adjuvant temozolomide. A blood score built on the levels of MDH1 and RNH1 expression was found to be an independent prognostic factor for survival based on the serum proteome data for a cohort of 96 IDH‐wildtype GB patients. This study highlights the utility of circulating MDH1 and RNH1 biomarkers for determining the prognosis of patients with IDH‐wildtype GB. Furthermore, the pathways driven by these biomarkers, and the tumor FABP7 pathway, may constitute promising therapeutic targets for blocking ROS detoxification to overcome resistance to chemoradiotherapy in potential GB STS.